2021
DOI: 10.3390/microorganisms9061317
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae Lipopolysaccharides Serotype O2afg Induce Poor Inflammatory Immune Responses Ex Vivo

Abstract: Currently, Klebsiella pneumoniae is a pathogen of clinical relevance due to its plastic ability of acquiring resistance genes to multiple antibiotics. During K. pneumoniae infections, lipopolysaccharides (LPS) play an ambiguous role as they both activate immune responses but can also play a role in immune evasion. The LPS O2a and LPS O2afg serotypes are prevalent in most multidrug resistant K. pneumoniae strains. Thus, we sought to understand if those two particular LPS serotypes were involved in a mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…The various O2 subtypes are associated with specific combinations of O loci (O1/O2v1, O1/O2v2 and a novel locus identified in the O2aeh type strain, here called O1/O2v3) with/without additional genes located elsewhere in the genome (wbbY, gmlABD and wbmVW [45,46], see Table 1). There is emerging evidence that these subtypes differ in terms of immunogenicity [15,17,47], but little is known about their distribution in the KpSC population, which may have implications for the design of vaccines or monoclonal antibody therapies targeting KpSC LPS.…”
Section: Impact Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The various O2 subtypes are associated with specific combinations of O loci (O1/O2v1, O1/O2v2 and a novel locus identified in the O2aeh type strain, here called O1/O2v3) with/without additional genes located elsewhere in the genome (wbbY, gmlABD and wbmVW [45,46], see Table 1). There is emerging evidence that these subtypes differ in terms of immunogenicity [15,17,47], but little is known about their distribution in the KpSC population, which may have implications for the design of vaccines or monoclonal antibody therapies targeting KpSC LPS.…”
Section: Impact Statementmentioning
confidence: 99%
“…While few prior studies have distinguished between O2 subtypes, a recent re-analysis of 573 KpSC genome sequences [28] indicated that 42 % of the 387 genomes carrying an O1/O2 O locus were predicted to express O2afg, followed by O1, a small number O2a or O2ac, and no O2aeh [46]. Additionally, the O2afg antigen has been previously associated with the ST258, ST512 and ST307 clones [15,47]. It has been suggested that the lower immunogenicity of O2afg, compared to O2a and O1, may provide a selective advantage that has facilitated the widespread dissemination of these clones, i.e.…”
Section: O Locus and O Type Distributionsmentioning
confidence: 99%
“…To determine whether the effect of KebOM was due to LPS content, we performed a comparison of LPS stimulation in organoids. The reported LPS levels in Klebsiella is 300–500 ng/μL 53 . Since we added 3.2 μg of KlebOM antigen (15 μg/mL) to the culture, the anticipated LPS in KlebOM is ~100 ng in the organoids, corresponding to a 500 ng/mL concentration.…”
Section: Resultsmentioning
confidence: 98%
“…The reported LPS levels in Klebsiella is 300-500 ng/μL. 53 Since we added 3.2 μg of KlebOM antigen (15 μg/mL) to the culture, the anticipated LPS in KlebOM is ~100 ng in the organoids, corresponding to a 500 ng/mL concentration. We observed that KlebOM induced significantly higher early MBCs than 500 or 1000 ng/mL of pure LPS.…”
Section: Il9 Temporally Regulates the Expression Of Epigenetic Marker...mentioning
confidence: 98%
“…In this work, we used K. pneumoniae carbapenemase KPC-producing strain, mentioned above as KPC-Kp, and an E. coli NDM-1/OXA-48 strain, described in the text above as E. coli-CR. These strains were collected from in-patients at our hospital and were previously characterized, including their multidrug resistance phenotype, elsewhere [ 55 , 56 ].…”
Section: Methodsmentioning
confidence: 99%